Influence of Experiential Dining Spaces on Enhancing the Flavours of Culinary Experience in Carnatic Regions of India - Pavithran, Anupama; Vaideeswaran, Akshaya (MAJ - Malaysia Architectural Journal, 2025)
In the Carnatic regions of India, where the food culture and the culinary landscape are deeply ingrained in the heart and soul of its people, restaurants have always been pivotal in shaping the dining experiences of individuals worldwide. Even in the post-pandemic era, with the promotion of in-home dining through online platforms, there remain certain irrefutable advantages to dining out in restaurants, drawing consumers to these establishments. Current trends indicate that in addition to food quality and pricing, today's customers also expect restaurants to address their social needs by providing experiential socialization. Consequently, the design of such experiential dining spaces has become a prerequisite for transforming commercial spaces into a sought-after commodity for consumers. This study employs a mixed-method approach, combining data from literature reviews, case studies, and a questionnaire survey to explore the interior design elements that enhance the diner's experience, with a specific focus on heritage-themed restaurants and the factors responsible for elevating the overall culinary experience, particularly in the Carnatic regions of India. The study proposes a conceptual model that defines 3 attributes of restaurant interiors (Spatial Cognition, Spatial Appreciation and Spatial Ambience) as the major antecedents affecting User experience within a Heritage-themed restaurant. The model is further validated based on the data collected through a questionnaire survey using Structural Equation Modelling (SEM). Theoretical possibilities are also briefly discussed.